Innovation Utilizing AI-Based Virtual Assistants for Employee Training and Development - Tri Cicik Wijayanti; Aditya Dandy Firatama; M Jamal Abdul Nasir; Aji Saptaji (Jurnal Manajemen, 2026)
This study examines the effectiveness of using AI-based virtual assistants in employee training and development. Employing a quantitative approach, data were collected through an online survey of 150 respondents working in various companies in Gresik Regency. The study aims to evaluate employees' perceptions of AI-based virtual assistants, focusing on their effectiveness, ease of use, learning experience, motivation, and impact on skill enhancement and productivity. Descriptive analysis revealed positive perceptions across all measured aspects, with average Likert scale scores above 4.0, indicating strong acceptance of thistechnology. Pearson correlation analysis showed significant positive relationships among the variables, suggesting that a positive perception of one aspect correlates with positive perceptions of others. Multiple linear regression analysis identified "Learning Experience through Virtual Assistants" as the most significant predictor of employee performance improvement. These findings highlight the potential of AI in enhancing employee training and development programs, providing valuable insights for HR practitioners and policymakers in designing more effective training strategies.